The Changes in Business Culture after the COVID-19 Pandemic in Indonesian Perspective - Hamdan, H; Junaedi, I Wayan Ruspendi; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2020)
The COVID 19 virus that hit the world not only caused damage to the health and safety of human souls but also had a very large impact on businesses in Indonesia. The impact of business is by decreasing people’s purchasing power, decreasing consumers, causing companies to experience failure, and eventually terminating employment. The goal is to find out to what extent the impact of COVID 19 has changed the business culture in Indonesia. This research uses descriptive qualitative research where the research uses interview sources and the results are explored with a literature approach through expert studies and other scientists. The results of the study explain that the approach and approach taken by business people have changed, especially in the areas of sales methods, approaching buyers, and also marketing strategies.